2014
DOI: 10.1109/tcpmt.2014.2326798
|View full text |Cite
|
Sign up to set email alerts
|

Airgap Interconnects: Modeling, Optimization, and Benchmarking for Backplane, PCB, and Interposer Applications

Abstract: Frequency and time domain models are developed for backplane (BP), printed circuit board (PCB), and silicon interposer (SI) links using six-port transfer matrices (ABCD matrices) for bumps, vias and connectors, and coupled multiconductor transmission lines for traces. The six-port transfer matrix approach enables easy computation of the transfer function, as well as near-end and far-end crosstalk. The intersymbol interference is accounted for by computing the pulse response for the worst case bit pattern. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Packages for future, high-performance IC packages are especially challenged because of the simultaneous demand for a reduction in energy per bit and an increase in signal speed. Kumar et al modeled the performance gains of embedded air cavities in organic IC packages [11]. They found that the optimal bandwidth density (bits per second/interconnect width) with an air-cavity interposer could be increased by as much as 70Â compared to an organic PCB.…”
Section: Introductionmentioning
confidence: 99%
“…Packages for future, high-performance IC packages are especially challenged because of the simultaneous demand for a reduction in energy per bit and an increase in signal speed. Kumar et al modeled the performance gains of embedded air cavities in organic IC packages [11]. They found that the optimal bandwidth density (bits per second/interconnect width) with an air-cavity interposer could be increased by as much as 70Â compared to an organic PCB.…”
Section: Introductionmentioning
confidence: 99%
“…Based on most recent on-chip interconnect and PCB interconnect studies in [43], [44], 40fJ/bit/mm for on-chip interconnect and 30pJ/bit/cm for PCB interconnect are used as I/O overhead. For core-memory distance, 10mm is assumed for on-chip case and 10cm is assumed for PCB trace length, both according to [43], [44]. Table III compares ELM-SR in both proposed in-memory computing platform and GPP platforms.…”
Section: System Level Evaluation Of Domain-wall Logic and Memorymentioning
confidence: 99%
“…Hardware-based accelerator is currently practiced to assist machine learning. In traditional hardware accelerator, there is intensive data migration between memory and logic [Kumar et al 2014;Park et al 2013] caused both bandwidth and power walls. Therefore, for data-oriented computation, it is beneficial to place logic accelerators as close as possible to the memory to alleviate the I/O communication overhead .…”
Section: Introductionmentioning
confidence: 99%